THE EFFECTIVENESS OF SELF-CREATED PICTURE VOCABULARY (SCPV) IN MOBILE-ASSISTED VOCABULARY LEARNING FOR JUNIOR HIGH SCHOOL STUDENTS - Roni Sita Widyastuti; Dwita Laksmita Rachmawati (University of Kuningan, 2026)
Vocabulary mastery is central to language learning success, yet traditional instructional approaches have consistently failed to promote durable retention among junior high school learners. Mobile-assisted language learning (MALL) offers promising alternatives by leveraging learner familiarity with mobile devices to create flexible, engaging learning environments. Despite theoretical support for combining visual learning with self-generated content in mobile contexts, empirical research specifically examining the Self-Created Picture Vocabulary (SCPV) approach remains limited, particularly for junior high school vocabulary instruction. This study investigated the effectiveness of SCPV in improving vocabulary mastery across four dimensions: word recognition, meaning comprehension, spelling accuracy, and contextual usage. A quasi-experimental pre-test and post-test design was employed with 64 eight-grade EFL students over a four-week SCPV intervention using a mobile application. Paired-samples t-tests revealed statistically significant improvements across all dimensions (p < .001), with a very large overall effect size (d = 2.31) and a mean score increase of 22.58 points (41.6%). Meaning comprehension showed the greatest gains (d = 1.97), followed by contextual usage (d = 1.42), word recognition (d = 1.28), and spelling accuracy (d = 1.06), SCPV integrating dual coding, generative learning, personalization, and mobile affordances constitutes an effective and practical approach to vocabulary instruction that warrants broader adoption in EFL classroom.